Coordination of sanitation investment decisions with broader water resources management - Dalcin, Ana Paula; Marques, Guilherme Fernandes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Water pollution affects water security, reducing water supply to economic water uses and threatening environmental preservation and human health. Controlling water pollution depends on efforts on two main sectors. One is water management, which provides regulatory instruments, including water quality standards, water abstraction and water discharge permits, as well as economic instruments, like water and wastewater charges. Another is sanitation, which is responsible for expansion of water and wastewater infrastructure and faces challenges in financing extensive infrastructure. While water management defines broader (watershed scale) strategies to address water quality, other decisions regarding infrastructure investment are made by the sanitation sector at the municipality scale, with limited perception of broader watershed context on water availability and pollution. When water management and sanitation decisions are not coordinated there are missed opportunities to (a) meet water quality standards at given river reaches due to lacking investment upstream and (b) find least cost investment solutions across municipalities, at the watershed scale. In this paper, we present methods and solutions to coordinate wastewater infrastructure expansion planning with water management instruments in the long-term planning to maximize economic returns and improve water quality. Our methods identify the regions where investments could be prioritized, coordinated with the distribution of water permits and definition of water quality targets. Results show that restricting water permits on some watershed regions results in a small water availability trade-off for economic uses but a significant reduction in costs to sanitation investments, while also meeting the water quality targets. We conclude that while there are several ways to reach predefined water quality targets, each way requires well-coordinated decisions from the water management perspective (where and when to allocate water permits) and the sanitation sector (where and when to concentrate investments in wastewater treatment). Thus, as important as the decisions to improve water management instruments and to increase investments in sanitation is their coordination towards a common watershed goal